2021
DOI: 10.1007/s40843-021-1653-y
|View full text |Cite
|
Sign up to set email alerts
|

Oriented inorganic perovskite absorbers processed by colloidal-phase fumigation

Abstract: Inorganic perovskite absorbers are promising candidates for next-generation photovoltaics due to their good thermal and light stabilities. Halide-mixed CsPbI x Br 3−x reach a compromise between its structural tolerance and absorption edge, yet the power conversion efficiencies (PCEs) of the asfabricated cells can be considerably limited by the nonideal quality of solution-processed films. Here we demonstrated a fumigation strategy on colloidal perovskite films using dual-O-donor ethyl acetate (EA). By in-situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Ideality factor (n) of the devices can be inferred by the slope of V OC as a function of light intensity employed to judge the dominant recombination mechanism [50,51] The values of n were estimated to be 1.43 and 1.22 for the pristine and PEAI-doped devices, indicating the suppressed nonradiative recombination of the PEAI-doped device. [52] Electrochemical impedance spectroscopy was further performed to evaluate carrier kinetics of PSCs. The Nyquist plots of pristine and PEAI-doped devices and the recombination resistance (R rec ) under different bias voltages are depicted in Figure S9a,b in the Supporting Information, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ideality factor (n) of the devices can be inferred by the slope of V OC as a function of light intensity employed to judge the dominant recombination mechanism [50,51] The values of n were estimated to be 1.43 and 1.22 for the pristine and PEAI-doped devices, indicating the suppressed nonradiative recombination of the PEAI-doped device. [52] Electrochemical impedance spectroscopy was further performed to evaluate carrier kinetics of PSCs. The Nyquist plots of pristine and PEAI-doped devices and the recombination resistance (R rec ) under different bias voltages are depicted in Figure S9a,b in the Supporting Information, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A dozen works have shown that the environmental stability of perovskites is closely related to crystallization processes or deposition techniques. [40,[133][134][135] Thermal annealing is a conventional procedure to obtain crystalline materials and is a crucial step in PSCs. It is typically operated under 100-150 C for 10-60 min to obtain high-quality films.…”
Section: Crystallinitymentioning
confidence: 99%
“…[ 5 ] The typical PSCs compose of perovskite absorbers, charge transport materials, and metallic contacts, in which the charge transport materials selectively extract the charge carriers and block the counter charges. [ 6 ] Recent progress in power conversion efficiency (PCE) heavily depended on the advancement of electron transport layers, such as the synthesis of n‐type SnO 2 [ 7 ] or TiO 2 . [ 8 ] In contrast, the inorganic hole transport layers (HTLs) have made very limited success, whose efficiencies were generally lower than that of the organic ones.…”
Section: Introductionmentioning
confidence: 99%